Potentiation of a neuronal nicotinic receptor via pseudo-agonist site - Mazzaferro, Simone (Cell Mol Life Sci, 2019)
Neuronal nicotinic receptors containing α4 and β2 subunits assemble in two pentameric stoichiometries, (α4)(3)(β2)(2) and (α4)(2)(β2)(3), each with distinct pharmacological signatures; (α4)(3)(β2)(2) receptors are strongly potentiated by the drug NS9283, whereas (α4)(2)(β2)(3) receptors are unaffected. Despite this stoichiometry-selective pharmacology, the molecular identity of the target for NS9283 remains elusive. Here, studying (α4)(3)(β2)(2) receptors, we show that mutations at either the principal face of the β2 subunit or the complementary face of the α4 subunit prevent NS9283 potentiation of ACh-elicited single-channel currents, suggesting the drug targets the β2–α4 pseudo-agonist sites, the α4–α4 agonist site, or both sites. To distinguish among these possibilities, we generated concatemeric receptors with mutations at specified subunit interfaces, and monitored the ability of NS9283 to potentiate ACh-elicited single-channel currents. We find that a mutation at the principal face of the β2 subunit at either β2–α4 pseudo-agonist site suppresses potentiation, whereas mutation at the complementary face of the α4 subunit at the α4–α4 agonist site allows a significant potentiation. Thus, monitoring potentiation of single concatemeric receptor channels reveals that the β2–α4 pseudo-agonist sites are required for stoichiometry-selective drug action. Together with the recently determined structure of the (α4)(3)(β2)(2) receptor, the findings have implications for structure-guided drug design.